Influence of drying conditions on the rheological properties of prunes - Gabas, A. L.; Menegalli, F. C.; Ferrari, F.; Telis-Romero, J. (Marcel Dekker Inc, 2002)
Rheological properties of rehydrated prunes were obtained applying compression-relaxation tests by using a Texture Analyzer TAXT2i. A mathematical development was adopted to determine the stress and area, along the deformation. Experimental data of stress versus time was fitted by using three different rheological models: generalized Maxwell, Normand & Peleg and Maxwell. Results showed that generalized Maxwell model can be used to describe the viscoelastic behavior of the samples. The rheological parameters obtained indicated that prunes exhibited elastic behavior more pronounced at low moisture content and drying air temperature. At high moisture content and temperature the sample became a more viscous and less rigid.
Keywords: fruit; relaxation behavior; rheological model; viscoelastic properties